Water is an instrument for peace, progress and prosperity - Tripathi, Mansi; Sikka, Alok; Sahana, V. (International Water Management Institute, 2024)
Tackling water security in India requires a multifaceted strategy including individual acts, community involvement, as well as government policies, programs and regulations.